Population-Level Impact of Omitting Axillary Lymph Node Dissection in Early Breast Cancer Women: Evidence from an Economic Evaluation in Germany - Hoa Thi Nguyen; Manuela De Allegri; Jörg Heil; André Hennigs (Applied Health Economics and Health Policy, 2022)
Background: The American College of Surgeons Oncology Group Z0011 trial showed that complete axillary lymph node dissection (cALND) did not improve survival benefits in patients with one or two tumour-involved sentinel lymph nodes and undergoing breast conservation. Still, a considerable number of the Z0011-eligible patients continue to be treated with cALND in various countries. Given the potential economic gain from implementation of the Z0011 recommendations, we quantified population-level impacts of omitting cALND among Z0011-eligible patients in clinical practice. Methods This 2-year economic analysis adopted both the perspective of patients under statutory insurance and the societal perspective, using data collected prospectively from 179 German breast cancer units between 2008 and 2015. The estimation of cost savings and health gain relied on a single decision tree, which considered three scenarios: clinical practice at the baseline; actual implementation in routine care; and hypothetical full implementation in all eligible patients. Results Data for 188,909 patients with primary breast cancer were available, 13,741 (7.3%) of whom met the Z0011 inclusion criteria. The use of cALND decreased from 94.3% in 2010 to 46.9% in 2015, resulting in a gain of 335 quality-adjusted life-years and a saving of EUR50,334,756 for the society. Had cALND been omitted in all eligible patients, the total gain would have been more than double. Conclusions The implementation of the Z0011 recommendations resulted in substantial savings and health gain in Germany. Our findings suggest that it is beneficial to introduce additional policy measures to promote further uptake of the Z0011 recommendations in clinical practice.
Keywords: 610; Medical and Health Sciences